Assessment of Business Education Lecturers on Instructional Delivery in Colleges of Education in Kaduna and Kano State - Haruna Hassan; Abdulrazak Mohammed (Universitas Ahmad Dahlan, 2022)
The study assessed the business education lecturers on instructional delivery in colleges of education in Kaduna and Kano State. Two research questions guided the study and two null hypotheses were formulated and tested at a 0.05 level of significance. The descriptive survey research design was used for the study. The population of the study comprised 32 business education lecturers from the Federal Colleges of Education, Kano (FCE Kano and FCE (T) Bichi), Kano State College of Education, Kumbosto, Federal College of Education, Zaria and Kaduna State College of Education, Gidan-Waya, Kaduna State. Since the population size is manageable, the researchers used all populations, and so, there was no sample size for the study. The researchers developed a structured questionnaire for data collection. The instrument was validated by two experts from the rank of senior lecturer and above from the business education department of Ahmadu Bello University, Zaria. Cronbach Alpha method was used to test the reliability of the instrument which yielded a coefficient value of 0.90. Mean and standard deviation was used to answer the research questions while Analysis of Variance (ANOVA) was used to test the two null hypotheses formulated for the study at a significance of the level of 0.05. The findings revealed among others that Business education lecturers give prompt feedback on students learning outcomes. Based on the findings of the study, it was recommended among others that, the college authority should employ more lecturers in the area of business education programmes for comprehensive curriculum delivery to the students.